The effects of supplementation with Gliricidia sepium or Leucaena leucocephala forage on intake, digestion and live-weight gains of Bos taurus X Bos indicus steers offered Napier grass - Abdulrazak, S.A.; Muinga, R.W.; Thorpe, W.R.; Orskov, E.R. (Cambridge University Press, 1996)
Two experiments were carried out to evaluate the effect of incremental levels of Gliricidia sepium (gliricidia) and Leucaena leucocephala (leucaena) on forage intake, diet apparent digestibility, microbial nitrogen supply and live-weight changes in cattle. In each experiment, 20 intact and five fistulated crossbred steers (Bos taurus X Bos indicus) were used. Napier grass basal diet was offered ad libitum alone or supplemented with 7.5, 15, 22.5 or 30 g dry matter (DM) per kg metabolic body weight (M 0.75) gliricidia (experiment 1) or leucaena (experiment 2). In experiment 1, total DM intake increased but not significantly with gliricidia supplementation (5.2, 5.1, 5.2, 5.4, 5.7 (s.e.d. 0.21) kg/day) while intake of napier grass was depressed linearly (5.2, 4.7, 4.5, 4.3, 4.2 (s.e.d. 0.21) kg/day; P<0.05). In experiment 2, supplementation with leucaena increased the total DM intake linearly without depressing the intake of napier grass (5.2, 5.8, 6.2, 6.6, 6.7 (s.e.d. 0.31) kg/day; P<0.001 and 5.2, 5.3, 5.3, 5.3., 5.0 (s.e.d. 0.21) kg/day respectively). Neither gliricidia nor leucaena supplementation affected the apparent digestibility of the diet or in sacco DM degradation characteristics of the forages. Rumen ammonia and live-weight gain were increased linearly (P<0.05) by supplementation from 130 to 215 mg/l (experiment 1) and 75 to 113 mg/l (experiment 2), from 306 to 478 g/day (experiment 1) and from 538 to 850 g/day (experiment 2), respectively. However, since the responses were linear, further experiments are required to quantify the responses to higher levels of these legume supplements.